(untitled) (Research, Society and Development, 2021)
The objective of the present study was to characterize raw materials and biochars produced under laboratory conditions, in addition to providing information regarding the feasibility of using biochar in the soil. Thus, in first stage, the biochar was produced from the dry sample of biosolids (BP) and sugarcane bagasse (BCP), by means of slow pyrolysis at a temperature of 350°C for 30 minutes. In a second stage, the characterization of the raw materials and their respective biochars was carried out. A design with five replications was used, and the treatments consisted of: pure biosolid; pure sugarcane bagasse; biosolid biochar (BB); sugarcane bagasse biochar (BBC). Where the assessment of residues was through the analysis of: mass yield, immediate, hydrogen potential, cátion exchange capacity, nutriente contente, X-ray fluorescence spectrometry, bromatology, particle density and size. The data obtained were submitted to analysis of variance (ANOVA) by the SISVAR program. To compare means, the Tukey testa t 5% probability (p<0,05) was used. It is concluded that both the raw materials and the biochars, produced by slow pyrolysis at 350°C, presented characteristics favorable for agricultutural use, mainly in terms of fertility.